2006
DOI: 10.4269/ajtmh.2006.75.994
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Distribution of Hantaviruses in Thailand and Potential Human Health Significance of Thailand Virus

Abstract: Phylogenetic investigations, sequence comparisons, and antigenic cross-reactivity studies confirmed the classification of Thailand virus (THAIV) as a distinct hantavirus species. The examination of sera from 402 rodents trapped in 19 provinces of Thailand revealed that five greater bandicoot rats (Bandicota indica) and one lesser bandicoot rat (B. savilei) from four provinces were focus reduction neutralization test (FRNT) antibody-positive for THAIV. One of 260 patients from Surin province in Thailand (initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
45
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 30 publications
(49 reference statements)
1
45
0
Order By: Relevance
“…Phylogenetic analysis shows that at least nine clades of HTNV and five clades of SEOV are prevalent in China Zou et al, 2016), including the Xinyi and Fugong viruses that have been recently reported in specific epidemic foci (Ge et al, 2016;Gu et al, 2016). Rodent-borne hantaviruses have also been detected in Lao PDR, Thailand (Thailand hantavirus, THAIV) and Cambodia (THAIV-like virus) (Blasdell et al, 2011;Pattamadilok et al, 2006). Among those viruses, THAIV can cause disease in humans (Pattamadilok et al, 2006;Gamage et al, 2011).…”
Section: Pathogenic Hantaviruses and Their Reservoirsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenetic analysis shows that at least nine clades of HTNV and five clades of SEOV are prevalent in China Zou et al, 2016), including the Xinyi and Fugong viruses that have been recently reported in specific epidemic foci (Ge et al, 2016;Gu et al, 2016). Rodent-borne hantaviruses have also been detected in Lao PDR, Thailand (Thailand hantavirus, THAIV) and Cambodia (THAIV-like virus) (Blasdell et al, 2011;Pattamadilok et al, 2006). Among those viruses, THAIV can cause disease in humans (Pattamadilok et al, 2006;Gamage et al, 2011).…”
Section: Pathogenic Hantaviruses and Their Reservoirsmentioning
confidence: 99%
“…Rodent-borne hantaviruses have also been detected in Lao PDR, Thailand (Thailand hantavirus, THAIV) and Cambodia (THAIV-like virus) (Blasdell et al, 2011;Pattamadilok et al, 2006). Among those viruses, THAIV can cause disease in humans (Pattamadilok et al, 2006;Gamage et al, 2011). Epizootiology studies have reported the presence of rats in Vietnam and Singapore with antibodies against SEOV (Truong et al, 2009;Johansson et al, 2010).…”
Section: Pathogenic Hantaviruses and Their Reservoirsmentioning
confidence: 99%
“…In other East Asian countries, such as Thailand, Indonesia, Vietnam, Sri Lanka and India, prevalence of SEOV and THAIV infection has been shown among rodents and humans [2,3,6,13,14,16,17,22].…”
mentioning
confidence: 99%
“…The predominant reservoir rodent species of PUUV is Myodes glareolus, which is classified into subfamily Arvicolinae. The predominant reservoir rodent species of SEOV, THAIV, HTNV and DOBV are Rattus norvegicus, Bandicota indica, Apodemus agrarius and A. flavicollis, respectively [13,18,20], and they are all classified into subfamily Murinae. Despite the close associations between rodent hosts and hantaviruses, exceptional host switching and spillover cases have been reported [26,27].…”
mentioning
confidence: 99%